Goals in the dual credit classroom: language as dual credit power - Armstrong, David Lee, author; Souder, Donna, advisor; Taylor, Ted, committee member; DeWitt, Debra, committee member (Colorado State University. Libraries, 2013)
From pen-to-paper submission to plagiarism filters such as Turnitin.com, Composition instruction tools change, and instructors at every level must adapt to technological advances. Despite changes at all levels, students' ability to manipulate language and manipulate the means of publishing language still equates to academic power. Manipulating technology and language, students and instructors alike must raise their expectations for both Composition product and process. In the Colorado high school classroom these raised expectations are called "21st Century Skills"1. These skills guarantee that a student can manipulate language and acquire the necessary language-based power to thrive in the 21st Century workplace. Post-Secondary institutions also include technology and the same "21st Century skills" in their outcomes for Composition I. Pierre Bourdieu's explanation of language as power2 is my basis for examining Composition expectations in College Composition I and High School Senior English in Colorado to provide dual credit3 classroom goals with college-level rigor combined with the rigid requirements of a high school setting. Scholars and high school administrators rarely examine dual credit classrooms and their academic product. They overlook dual credit students because they represent the school's elite and adhere to rules or regulations teachers place on them. But their learning takes second or even third place to students who don't perform as well, but who still follow the same rules and regulations. In a Colorado high school classroom, CCSS provide content and expectations to aid students in academic growth. Nevertheless, college Composition classrooms do little more than prepare students to teach Composition or provide a base for scaffolding further Composition instruction. Neither the CCSS nor the Composition I outcomes prepare the dual credit student for their next academic step. Several P-Post-Secondary Composition advocates, high school Composition advocates, and Post-Secondary Composition advocates outline Composition requirements and outcomes at their particular level of academia. My analysis includes the National Council of Teachers of English expectations for the teaching of writing, the Council of Writing Program Administrators, the Colorado Community College System, and the Colorado Common Core State Standards. After I analyze what these experts identify as Composition, I examine college Composition theory according to James Berlin and Kathleen Blake Yancey. Berlin provides a historical view of college Composition, and I juxtapose his view with Yancey who provides a modern, technological, communication based4 expectation of the Composition Classroom. Lastly, anecdotal evidence and pedagogical strategies from my own high school classroom provide first-hand credible evidence of assessment and expectation in a dual credit classroom. Finally, I argue for Bourdieu-centered goals that provide dual credit students with meaningful instruction that provides college-level rigor with accommodated protection of a high school learning environment including but not limited to: image analysis, technology access, theme and unit study, and rigorous Composition expectations.
Keywords: concurrent; Bourdieu; composition; dual-credit; secondary; Yancey